# Solve the inequality : 3(6b-1) > 18 - 3b

*print*Print*list*Cite

### 2 Answers

3(6b-1) > 18 - 3b

First we will factor 3 from the right side:

==> 3 ( 6b -1) > 3 ( 6-b)

Now divide both sides by 3:

==> (6b -1) > (6-b)

Now add b to both sides:

==> 6b -1 + b > 6 - b + b

==> 7b -1 > 6

Now add 1 to both sides:

==> 7b > 7

Now divide by 7:

==> b > 7/7

==> b> 1

Then the solution for the inequality is all real numbers greater that 1.

**==> b belongs to the interval : ( 1 , inf ) **

We'll factorize by 3 to the right side:

3(6b-1) > 3(6 - b)

We'll divide by 3:

6b-1>6-b

We'll subtract 6-b both sides:

6b - 1 - 6 + b > 0

We'll combine like terms:

7b - 7 > 0

We'll factorize by 7:

7(b-1)>0

We'll divide by 7:

b-1>0

b>1

**The interval of admissible values for b is:(1, +infinite)**